(untitled) (OverHolland, 2008)
Placing the railway that runs through Gouda underground means more than just removing a physical barrier in the city. While in other cities of this design research the rail path cuts through a more or less continuous structure, in Gouda the railway line at station level is simply a line separating different structures. Making the rails disappear from ground level will result in two entirely different districts, the historical and 19thcentury city on the one side and the postwar city on the other, which will suddenly confront one another. In the case of Gouda, a design study of the spatial possibilities of placing the railway line underground is actually research on a connection: how can a space that separates be converted into a space that connects?